Challenges of Women Entrepreneurship and Empowerment in South Africa: Evidence from Rural Areas - NHLEKO, Mary-Ann Nokulunga; MSOMI, Thabiso Sthembiso; OGUNSOLA, Sijuwade Adedayo (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to identify impediments to expanding women-owned businesses in rural areas of South Africa. The study used a quantitative research method to collect data. The study concentrated on 250 female business owners in the rural communities of Hluhluwe, Ulundi, and Eshowe in northern KZN. The study found that the main obstacles to expanding women-owned businesses in rural areas were financial constraints, a lack of education, and inadequate infrastructure. However, these difficulties experienced by women business owners in rural South Africa can be conquered. Overcoming these obstacles could empower women entrepreneurs and stimulate economic growth in rural areas, thus reducing poverty and enhancing the living standards of rural communities. Based on these findings, the study recommends various interventions, such as alternative financing models, targeted education and training programs, and infrastructure development, to support the growth of women-owned enterprises in rural areas. Future research should examine additional issues such as cultural and social hurdles, a lack of access to markets and information, and legal and regulatory restrictions that impede the establishment of women-owned businesses in rural areas.